PERAN HUMAS UNIVERSITAS UDAYANA DALAM PENGELOLAAN INFORMASI PUBLIK - Dewi, Tasya Semara; Purnawan, Ni Luh Ramaswati; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 6 No 1 (2025): Jurnal Ilmu Komunikasi Vol 6 No 1 Tahun 2025, 2025)
Abstract Udayana University realizes openness of public information through the establishment of PPID and using the website (www.unud.ac.id) as the main medium for providing public information. PPID appointed Public Relations of Udayana University as an auxiliary unit. Public Relations, which was restructured in 2017 as a subsection under BAKH, has the task and function of managing information. This study aims to look at the role of public relations in managing public information on the Udayana University website. The research method used is a descriptive qualitative approach with data collection through interviews, observation and documentation studies. The results of the study show that Public Relations of Unud as a PPID auxiliary unit has control over the coverage, preparation and publication of news on the Unud Website. Public Relations coordinates with internal parties in compiling agendas for leadership activities and utilizes the SIRAISA and UPIKS information systems in gathering activities for other faculties/units. The minimum quantity of public relations human resources is a challenge in fulfilling coverage of activities on campuses that have far-flung areas. The quality of Public Relations human resources is also required to be creative in compiling news content in order to build a positive image of Unud in the eyes of the internal and external public.   Keywords: Public Information Disclosure, Udayana University Public Relations, SWOT Analysis